POLITENESS NORMS FOR HARMONIOUS COMMUNICATION WHEN SERVING TOURISTS IN CENTRAL JAVA - Purnomo, Budi (KOMUNITAS, 2014)
People in most cultures would probably agree that politeness is needed during their interaction. However there may be differing opinions as to when they should be polite. In tourism industry, tourism serviceproviders act as host and tourists act as guests. Typically hosts will try to act politely and use appropriate politeness norms whenÂ communicatingÂ withÂ guestsÂ toÂ ensureÂ harmonious communication.Â TheÂ researchÂ findingsÂ showÂ thatÂ thetourism service providers in Central Java use variousÂ unggah-ungguhâpoliteness normsâ when serving English speaking tourists and Indonesian speaking tourists.Besides that, there are some violations made by the tourism serviceÂ providersÂ inÂ usingÂ unggah-ungguhÂ âpolitenessÂ normsâ.Â TheÂ researchÂ findingsÂ alsoÂ show thatÂ thereÂ are similar and different perspectives onÂ unggah-ungguhâpoliteness normsâ between English speaking tourists with Western culture background and Indonesian speaking tourists with Indonesian culture backgrounds towards the politenessÂ normsÂ usedÂ byÂ theÂ tourismÂ serviceÂ providersÂ inÂ CentralÂ Java.Â TheÂ findingsÂ implyÂ theÂ needsÂ of improvingÂ unggah-ungguhÂ âpolitenessÂ normsâÂ implementationÂ whichÂ isÂ discoveredÂ fromÂ wellÂ knownÂ noble Javanese culture used by the tourism service providers when serving tourists. Keywords:politeness norms, harmonious communication, English and Indonesian tourists